Effect of Farmers' Characteristics, Forage Land and Water Availability for Dairy Milk Production in Boyolali, Central Java, Indonesia - Hidayah, Nurulia (2014)
This study is one part of the research potential of the dairy cattle development in Central Java Boyolali, Indonesia. This study aims to analyze the influence of the characteristics of dairy farmers, forage land and water availability on dairy cow milk production in Central Java Boyolali, Indonesia. This research was conducted from March 2010 until January 2011 in three dairy cooperatives: Mojosongo cooperatives, Musuk cooperative, and Cepogo cooperatives using the survey method. Total respondents used in this study were 266 farmers divided into three stratum. Primary data was collected through interviews based on a questionnaire that has been prepared. Data were analyzed using multiple linear analysis simple. The analysis showed that characteristics of dairy farmers, forage land and water availability together significantly influenced the milk production. At stratum R2 value of 0.965 suggesting that milk production could be explained by factors independent as much as 96.50 %, while the remaining 3.50 % is caused by other factors outside the model. At stratum II R2 value of 0.635 suggesting that milk production could be explained by factors independent as much as 63.50 %, while the remaining 35.50 % is caused by other factors outside the model. At stratum III R2 value of 0.681 suggesting that milk production could be explained by factors independent as much as 68.10 %, while the remaining 31.90 % is caused by other factors outside the model.